Injectable Hydrogels for 3D Bioprinting - Noh, Insup, 1961-; Wang, Xiumei (Biomedical engineer); Vlierberghe, Sandra van (Biomaterials science series, 2021)
Tightly edited, the reader will find this book to be a coherent resource to learn from. It will appeal to those working across biomaterials science, chemical and biomedical engineering, tissue engineering and regenerative medicine.